'Something extra': In defence of an uncanny humanism. Issue 1 (13th March 2022) - Cohen, Josh
Abstract: This article proposes literature and psychoanalysis as forms of critical education, putting in urgent question the market‐driven, instrumental models of learning that currently dominate higher education policy. In psychoanalytic terms, it argues, the primary mechanism at work in such a policy is what psychoanalysis calls splitting, which involves above all a kind of banishment of doubt and a rigid assurance in the rightness of the status quo that precludes meaningful change or transformation in the self and the world. The article goes on to identify in psychoanalysis and literature more 'unsplit' modes of thinking that refuse the reduction of the human being to a purely functional value. It ends with a reading of Kazuo Ishiguro's Never Let Me Go as a critical meditation on this reductive tendency.